Are dietary modifications effective for preventing gout attacks?. Issue 1 (January 2016) - Rodriguez, Cesar B.; Bhattacharyya, Adity
Abstract : Evidence‐Based Answer : Increased coffee consumption is associated with reduced gout flares (SOR: B, longitudinal study). Consumption of animal‐based purines and, to a lesser extent, plant‐based purines increases the risk of gout flares (SOR: B, longitudinal study).